2022
DOI: 10.1007/s00044-022-02900-3
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenyl substituted Benzimidazole derivatives: Design, synthesis, and evaluation of their antiproliferative and antimicrobial activities

Abstract: The inability to meet the desired outcomes of anticancer treatment and decrease in treatment success of bacterial and fungal infections accelerated research in these areas. Our research group has conducted numerous studies, especially on benzimidazole ring systems' antiproliferative and antimicrobial activities. In this study, the antiproliferative activity of benzimidazole compounds was tested against A549, A498, HeLa, A375, and HepG2 cancer cell lines by MTT assay. All compounds exhibited good to potent anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The other compounds (3cf, 3j-l) have little or no interaction with target protein binding residues. [32] These compounds' weak interactions with target proteins may be explained by the existence of several donor groups connected to and at various locations of these compounds. The varying orientations of attachment of different groups to the same chemistry change the capacity of these compounds to bind because the lack of these donating groups in compounds (3g-j).…”
Section: S No Compoundsmentioning
confidence: 99%
“…The other compounds (3cf, 3j-l) have little or no interaction with target protein binding residues. [32] These compounds' weak interactions with target proteins may be explained by the existence of several donor groups connected to and at various locations of these compounds. The varying orientations of attachment of different groups to the same chemistry change the capacity of these compounds to bind because the lack of these donating groups in compounds (3g-j).…”
Section: S No Compoundsmentioning
confidence: 99%
“…Ersan, Ronak Haj, et al [133] synthesized a new 2-Phenyl substituted Benzimidazole derivatives and evaluation of their biological activity as anticancer and antimicrobial.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Ersan et al 133 synthesized new 2-phenyl substituted benzimidazole derivatives and evaluated their biological activity as anticancer and antimicrobial agents (Figure 27 ). In the antimicrobial study, all compounds were tested to confirm their antimicrobial properties against gram-positive bacteria, gram-negative bacteria and fungi.…”
Section: Biological Activity Of Benzimidazole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 2 decades, the research on benzimidazole-containing antimicrobial drugs has gained the attention of many scientific groups. Ersan et al reported that 2-(benzyl/phenylethyl/phenoxymethyl) benzimidazole derivatives showed promising antimicrobial effects against Gram-positive bacteria and fungi but relatively low effects against Gram-negative bacteria . N-Substituted benzimidazoles 6 and 7 (Figure ) effectively inhibited the growth of methicillin-resistant Staphylococcus aureus MRSA ATCC4330 and USA 300, respectively, exhibiting minimal inhibitory concentration (MIC) values up to 4 μg mL –1 , and chemical substance 7 was identified to be bactericidal.…”
Section: Introductionmentioning
confidence: 99%